Land use and Europe’s renewable energy transition: identifying low-conflict areas for wind and solar development - Kiesecker, Joseph M.; Evans, Jeffrey S.; Oakleaf, James R.; Dropuljić, Kasandra Zorica; Vejnović, Igor; Rosslowe, Chris; Cremona, Elisabeth; Bhattacharjee, Aishwarya L.; Nagaraju, Shivaprakash K.; Ortiz, Anthony; Robinson, Caleb; Lavista Ferres, Juan M.; et al. (Frontiers in Environmental Science, 2024)
Continued dependence on imported fossil fuels is rapidly becoming unsustainable in the face of the twin challenges of global climate change and energy security demands in Europe. Here we present scenarios in line with REPowerEU package to identify Renewables Acceleration Areas that support rapid renewable expansion, while ensuring minimal harm to places important for biodiversity and rural communities. We calculated the area needed to meet renewable energy objectives under Business-as-Usual (BAU) and Low-conflict (LCON) development scenarios within each country, providing a broad overview of the potential for renewable energy generation to reduce impacts when development is steered toward lower conflict lands. Our analysis shows that meeting renewable energy objectives would require a network of land-based wind turbines and solar arrays encompassing upwards of 164,789 km2 by 2030 and 445,654 km2 by 2050, the latter roughly equivalent to the land area of Sweden. Our results highlight that BAU development patterns disproportionately target high-conflict land cover types. By 2030, depending on the development pathway, solar and wind development are projected to impact approximately 4,386–20,996 km2 and 65,735–138,454 km2 of natural and agricultural lands, respectively. As renewable energy objectives increase from 2030 to 2050 impacts to natural and agricultural lands also increase, with upwards of 33,911 km2 from future solar development and 399,879 km2 from wind development. Despite this large footprint, low-conflict lands can generate substantial renewable energy: 6.6 million GWh of solar and 3.5 million GWh of wind, 8–31 times 2030 solar objectives and 3–5 times 2030 wind objectives. Given these patterns, we emphasize the need for careful planning in areas with greater impact potential, either due to a larger demand for land area or limited land availability. Top-emitting countries with large renewable energy objectives (Germany, Italy, Poland, France, Spain) and those with limited flexibility in meeting objectives on low-conflict land (Albania, Slovenia, Montenegro, Hungary, Croatia, Serbia, Bosnia Herzegovina, Finland, Greece, Portugal, and Norway) should be priorities for country-level customizations to guide low-conflict siting and avoid disproportionate impacts on high-value areas.